Sports Facilities and Social Responsibility: A Challenge for the Decade - Lucas, Susana (2011)
The last decade of the XX century consolidated a new vision of development that involved not only the natural environment, but also socio-cultural aspects in a prominent position, argued that the quality of life of human beings became the condition for progress. This proposal is based on sustainable development considering the preservation for future generation’s current use of natural resources. We cannot imagine the functioning of the developed societies without major hospitals, shopping malls, sports facilities, public transport stations, public institutions, schools, waste treatment plants etc.. The construction of such equipment involves huge amounts of money and produces a significant impact on the neighbourhood. These impacts on the economy, called externalities, can be positive or negative. Looking at the issue of community facilities from a macroeconomic point of view, a proper functioning of such equipment is essential for the development of local communities and general society. Amidst the global crisis, the best and most profitable use of such equipment enhances its positive impacts on society, which is supposed to be inclusive, and creates the structural conditions for social and economic growth. Many of those items can be better managed taking into consideration social sustainability by creating conditions for local and country development. A more inclusive and participatory society is one of the key objectives of Europe 2020. The EU commission has identified three elements for the growth of the European state in the coming years: smart growth, sustainable growth (making our production more efficient in terms of resources, while boosting our competitiveness), inclusive growth (increased rate of participation in the labour market, acquiring skills and the fighting poverty). For the success of this strategy for the next decade, it is essential to have a social vision of the market. Improved management of such equipment can create opportunities for civic engagement of local citizens, for education and even for the creation of micro-business around the equipment. The greater involvement of citizens also allows channelling the energies of many social groups to make the social goals comprehensive, providing the appearance of a more participatory society. Companies today face many management problems of social sustainability in its various dimensions such as: demographic changes, social justice, education, health, among others. The proper management approach has to be an answer on how to deal with these problems. The objective of our work is the introductory analyses of the state of art of the management for social sustainability objectives of the sports facilities in Portugal. After this introductory analysis, we will propose the creation of a methodological guide for managers of these public facilities, in order to include the social sustainability aspects on their task and management objectives.